2016
DOI: 10.1177/0363546515621890
|View full text |Cite
|
Sign up to set email alerts
|

Hips on Point

Abstract: Dancers with acetabular dysplasia usually have excellent turnout because of their shallow socket but ironically their hips contain the seeds of their own destruction.-William Hamilton, ''Ballet'' 9

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In women, there is a higher rate of acetabular dysplasia and elevated Beighton scores, permitting turnout. 33,34 Therefore, limb alignment may play a role in the risk for stress fracture. A recent systematic review found that elite ballet dancers had higher rates of lower extremity injury from pelvic malalignment, whereas recreational dancers had higher rates of lower extremity injury associated with poor spine alignment and increased hip range of motion.…”
Section: Risk Factors For Stress Injurymentioning
confidence: 99%
“…In women, there is a higher rate of acetabular dysplasia and elevated Beighton scores, permitting turnout. 33,34 Therefore, limb alignment may play a role in the risk for stress fracture. A recent systematic review found that elite ballet dancers had higher rates of lower extremity injury from pelvic malalignment, whereas recreational dancers had higher rates of lower extremity injury associated with poor spine alignment and increased hip range of motion.…”
Section: Risk Factors For Stress Injurymentioning
confidence: 99%